2006
DOI: 10.1063/1.2337254
|View full text |Cite|
|
Sign up to set email alerts
|

Thermal properties of carbon nanotube array used for integrated circuit cooling

Abstract: Carbon nanotubes ͑CNTs͒, owing to their exceptionally high thermal conductivity, have a potential to be employed in micro-and optoelectronic devices for integrated circuit ͑IC͒ cooling. In this study we describe a photothermal metrology intended to evaluate the thermal conductivity of a vertically aligned CNT array ͑VCNTA͒ grown on a silicon ͑Si͒ substrate. Plasma-enhanced chemical vapor deposition, with nickel ͑Ni͒ as a catalyst, was used to grow CNT. The experimentally evaluated thermal conductivity of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 32 publications
2
49
0
1
Order By: Relevance
“…The opportunity to reduce interfacial thermal inefficiencies through the use of CNT arrays considered herein would substantially enhance their reliability and utility. Previous studies [7][8][9][10][11][12][13][14][15][16] have demonstrated that multiwalled carbon nanotube (MWCNT) arrays grown on one side of an interface can achieve room-temperature thermal resistances as low as 7-25 mm 2 K/W, depending on the method of fabrication and array morphology. Using transient optical techniques, Wang et al [11], Cola et al [13], and Tong et al [14] revealed that the interfaces between MWCNTs and their growth substrate and the interfaces established at the free ends of MWCNTs can be significant thermal bottlenecks in MWCNT array interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportunity to reduce interfacial thermal inefficiencies through the use of CNT arrays considered herein would substantially enhance their reliability and utility. Previous studies [7][8][9][10][11][12][13][14][15][16] have demonstrated that multiwalled carbon nanotube (MWCNT) arrays grown on one side of an interface can achieve room-temperature thermal resistances as low as 7-25 mm 2 K/W, depending on the method of fabrication and array morphology. Using transient optical techniques, Wang et al [11], Cola et al [13], and Tong et al [14] revealed that the interfaces between MWCNTs and their growth substrate and the interfaces established at the free ends of MWCNTs can be significant thermal bottlenecks in MWCNT array interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Using transient optical techniques, Wang et al [11], Cola et al [13], and Tong et al [14] revealed that the interfaces between MWCNTs and their growth substrate and the interfaces established at the free ends of MWCNTs can be significant thermal bottlenecks in MWCNT array interfaces. Therefore, to promote good thermal contact at the MWCNT-growth substrate interface, adhesion layers (e.g., Ti, Mo, or Cr) are often deposited on the substrates before MWCNT fabrication [9][10][11][12][13][14][15]. Additionally, Tong et al [14] demonstrated that the resistance at the MWCNT free ends' interface, which was an order of magnitude higher than the resistance at the MWCNT-growth substrate interface, can be reduced up to an order of magnitude by using a thin layer of indium to weld the MWCNT ends to the opposing substrate.…”
Section: Introductionmentioning
confidence: 99%
“…51306108, 51176106), the Basic Research [29] Experiments CNT/CNT 50 nm 0.2e7 Â 10 À8 m 2 K/W Yang et al [30] Experiments CNT/Au >3.5 mm 2.1 Â 10 À7 m 2 K/W Xu et al [31] Experiments CNT-Cu 16 nm 4.0 Â 10 À8 m 2 K/W…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The estimated data from the result of Ref. [31] is in the calculation range (0.3e7.0 Â 10 À8 m 2 K/W).…”
Section: Length Dependence Of Thermal Conductivitymentioning
confidence: 99%
“…Nanotubes are also used to synthesize nanofluids which find applications in cooling and thermal storage technologies. Nanotubes have, therefore, been proposed for applications as nanofins to cool high heat flux electronic devices and as highly conducting thermal interface materials between microprocessor chips and heat sinks (Kordas et al 2007;Xu et al 2006Xu et al , 2007.…”
Section: Properties and Applications Of Carbon Nanotubesmentioning
confidence: 99%